Financeirização e ascensão das plataformas: um estudo de caso - Silva, Felipe Marques e (2024)
The financialization of the economy is a process observed since the last decades of the 20th century and has introduced the dynamics of financial markets where they did not exist before, altering the logic of supply chain management of organizations. These characteristics, combined with technological advancements, have contributed to the rise of companies such as Amazon, Facebook, Google, and Uber, which have created online structures that enable a wide range of human activities, promoting radical changes in how we work, socialize, create value in the economy, and compete for resulting profits. Understanding how these organizations function and the new dynamics brought about by financialization can have important implications for academia and society. Thus, the aim of this master's thesis was to explore the dynamics of financialization in the context of the emergence and rise of platform companies, focusing on implications for the organizational, economic, and social contexts. To achieve this, we conducted a systematic literature review following the PRISMA guidelines and lexical analysis using the iramuteq software to characterize the literature that addressed the topics of financialization and platform companies. Additionally, we conducted a single case study to observe the financialization process of the Uber company. The systematic review and textual analysis of the abstracts of the documents that comprised the sample identified 4 classes with the main themes addressed in the literature: Shareholder Value and Data Capitalism; Platforms and Gentrification; Sharing Economy, Neoliberalism, and Labor on platforms; and Platforms and Power. In the case study on Uber, we explored indicators previously brought by other authors and new indicators characteristic of platforms: Comparison between sources of profitability; Ownership composition and share acquisitions; Mergers and acquisitions; Origin of executives; Executive compensation payments; Dividend payments to shareholders; Employee salaries; Employment; Influence of Venture Capital; and Tax structure. The results showed that Uber exhibits typical characteristics of what the literature presents about financialization; however, it also presents other important aspects that deviate from trends highlighted in previous research, such as patient investment from venture capitalists in the company. We also observed that the financialization structure adopted by the company seems to be the main aspect responsible for the social and economic imbalances and inequalities observed in its structure, distorting its discourse of integration into the sharing economy. We understand that the exploration of this phenomenon is essential for the fields of economic sociology, which may have in its references, methodologies, and approaches the tools capable of unraveling the specificities and nuances brought by platforms and their operation from financialization.